Evaluation of layer diet formulated from non-conventional feeding stuffs - Ravindran V
A layer diet, the formulation of which was based on several non-conventional feedingstuffs, was evaluated at the research stationa dn under small farm conditions in Sri Lanka. The new feeding stuffs included finge millet, rice polishings, rubbber seed meal, cassava leaf meal, ipil ipil leaf meal and dried poultry manure. A commercial mash, that is normally used on the farm, served as the control.2. The performance and egg quality characteristics were similar between the test and control diets, the only exception being the egg yolk colour which was improved (P<0.05) by feeding the test diet. Food cost per dozen eggs was lowered by feeding the test diet. 3. It is possible to formulate layer diets using non-conventional feedingstuffs, achieve acceptable production and lower the food costs under small farm conditions in tropical developing countries.
Keywords: Diet; Hens; Rubber seed meal